Sabdatama dan Sabdaraja Sri Sultan Hamengku Buwono X dalam Perspektif Keistimewaan Daerah Istimewa Yogyakarta - Raisa Rizani (Universitas Islam Indonesia, 2016)
The issue of Sabdatama and Sabdaraja by Sri Sultan Hamengku Buwono X has created pros and cons both from the internal parties and external of Kraton (Kingdom). This research is to study two issues: first, what is the juridical implication with the issues of Sabdatama and Sabdaraja towards Regulation No. 13 of 2012 about the Specialty of Special District of Yogyakarta (DIY)? Second, can Sabdatama and Sabdaraja be as a reference in revising the Law of Specialty? The research method used is the normative-juridical method with the historical approach and the regulation approach. The result of this research concluded: first, the substances of Sabdatama and Sabdaraja are contradicting with the Specialty Regulation of Special District of Yogyakarta and is not included in the hierarchy of law and regulation and not as a source of constitutional law. Second, Sabdatama and Sabdaraja are not suitable if used as a base to change the Law of Specialty of Special District of Yogyakarta. Keyword: Sri Sultan Hamengku Buwono X, Law of Specialty of Special District of Yogyakarta (DIY), sabdatama, and sabdaraja